Retinoblastoma and ambient exposure to air toxics in the perinatal period - Heck, Julia E. (2013)
We examined ambient exposure to specific air toxics in the perinatal period in relation to retinoblastoma development. Cases were ascertained from California Cancer Registry records of children diagnosed 1990–2007 and matched to California birth certificates. Controls were randomly selected from state birth records for the same time period. We chose 27 air toxics for the present study that had been listed as possible, probable, or established human carcinogens by the International Agency for Research on Cancer. Children (103 cases and 30,601 controls) included in the study lived within 5 miles (~8K) of an air pollution monitor. Using logistic regression analyses, we modeled the risk of retinoblastoma due to air toxics exposure, separately for exposures in pregnancy and the first year of life. With a per interquartile range increase in air toxics exposure, retinoblastoma risk was found to be increased with pregnancy exposure to benzene (OR=1.67, 95%CI 1.06, 2.64) and other toxics which primarily arise from gasoline and diesel combustion: toluene, 1,3 butadiene, ethyl benzene, ortho-xylene, and meta/para-xylene; these 6 toxics were highly correlated. Retinoblastoma risk was also increased with pregnancy exposure to chloroform (OR=1.35, 95%CI 1.07, 1.70), chromium (OR=1.29, 95%CI 1.04, 1.60), para-dichlorobenzene (OR=1.24, 95%CI 1.04, 1.49), nickel (OR=1.48, 95%CI 1.08, 2.01), and in the first year of life, acetaldehyde (OR=1.62, 95%CI 1.06, 2.48). Sources of these agents are discussed.